THE INFLUENCE OF NEED FOR UNIQUENESS, BANDWAGON EFFECT AND REFERENCE GROUP ON PURCHASE INTENTION THROUGH VALUE-EXPRESSIVE FUNCTION OF ATTITUDE AS AN INTERVENING VARIABLE (EMPIRICAL STUDY ON HIJAB BUTTONSCARVES) - Meydiawati, Meydiawati; Pebrianti, Wenny; Ramadania, Ramadania (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Abstract: This research aims to analyze the influence of need for uniqueness, bandwagon effect, and reference group on purchase intention through the value-expressive function of attitude as an intervening variable on Buttonscarves hijab in Pontianak. The research approach is quantitative, using an associative causal method. The research is conducted on respondents who are familiar with Buttonscarves hijab products in Pontianak. Sampling in this research used non-probability sampling method, specifically purposive sampling. The collected data were then analyzed using Structural Equation Model with the assistance of the SmartPLS version 4 statistical application. The results of the data analysis indicate a direct and significant influence between the need for uniqueness and the bandwagon effect on the value-expressive function of attitude. The need for uniqueness, bandwagon effect, and reference group significantly influence purchase intention. The value-expressive function of attitude significantly influences purchase intention. The value-expressive function of attitude mediates the indirect influence of the need for uniqueness and the bandwagon effect on purchase intention. All hypothesis testing results show a strong level of significance and reliability. The implications of these findings underscore the importance for Buttonscarves to design marketing strategies that not only emphasize the exclusivity of the product but also capitalize on consumers' desire to express their personal values through the products they purchase. Keywords: Need For Uniqueness, Bandwagon Effect, Reference Group, Value-Expressive Function Of Attitude, Purchase Intention.